2010
DOI: 10.1007/s10549-010-1286-0
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase II study of pemetrexed as first-line chemotherapy in patients with advanced or metastatic breast cancer

Abstract: Palliation is the primary goal in metastatic breast cancer (MBC), and safe, efficacious, new single-agent options are needed. Pemetrexed, an antifolate, inhibits several folate-dependent enzymes involved in purine biosynthesis. The primary goal of this study was to determine the objective response rate in patients with advanced or MBC given pemetrexed as a first-line, dose-dense, every 2-week chemotherapy. Women with HER2-negative advanced or MBC, without prior cytotoxic treatment for this stage of disease, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…It has also demonstrated modest activity in previously untreated breast cancer [1]. Pemetrexed has been shown to have more than one mechanism of action in tumor cells as illustrated by the continued anti-proliferative effect of the drug in cells exposed to exogenous thymidine (which prevents the cytotoxic effects of thymidylate synthase inhibition) [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has also demonstrated modest activity in previously untreated breast cancer [1]. Pemetrexed has been shown to have more than one mechanism of action in tumor cells as illustrated by the continued anti-proliferative effect of the drug in cells exposed to exogenous thymidine (which prevents the cytotoxic effects of thymidylate synthase inhibition) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Initially used principally in the metastatic setting, the former two are increasingly part of adjuvant regimens. ixabepilone, 10 vinorelbine, 11 gemcitabine, 12 pemetrexed, 13 and the platinums. 14 In addition, the value of retreatment with an agent to which the patient has previously been exposed remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Via steps of screening the title and reading the abstract, 10 studies were identified (Amadori D 2013;Dittrich C 2012;Robert NJ 2011;Martin M.2009 When pemetrexed was used in second line chemotherapy, 5 studies included in this study are presented and the short-term outcomes suggested that the response rate of Deng et al (2013) (2001) was 26%. Totally, 513 patients were enrolled and 167 patients achieved CR or PR, the pooled response rate thus was 39/281 (13.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Grades 3-4 treatment-related toxicities included: neutropenia (36%), leukopenia (17%), fatigue (14%), and anemia (14%). Grade 1/2 alopecia was seen in 8% of patients (Robert et al, 2011).…”
Section: A Systemic Analysis On Pemetrexed In Treating Patients With mentioning
confidence: 98%